How Do Sharia Supervisory Board and Good Corporate Governance Relate to Islamic Banks Performance? - Rustam Hanafi; Abdul Rohman; Dwi Ratmono (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2021)
This study aims to investigate the relationship between the characteristics of the Sharia Supervisory Board (SSB) and Good Corporate Governance (GCG) on the performance of Islamic Banks (IBs). Data were collected from 14 IBs listed on the Financial Services Authority (OJK) during 2013–2019. The multiple regression results empirically show that SSB with the academic position as professor shows a significant positive relationship on IBs performance. Meanwhile, SSB with doctoral education has no positive relationship with IBs performance. Although it is not positively correlated, doctoral education is still needed but with a background in law or sharia education, economics including finance or accounting, and muamalah. Educational background is proven to have a significant positive relationship with IBs' performance. Meanwhile, SSB, which only has a finance or accounting background, does not positively affect IBs' performance. In addition, GCG shows a very significant positive relationship with the IBs' performance. It indicates that effective and efficient governance by the Board of Directors, Board of Commissioners, and SSB through implementing better GCG and sharia principles will improve IBs performance.==========================================================================================================ABSTRAK – Bagaimana Kaitan Dewan Pengawas Syariah dan Good Corporate Governance dengan Kinerja Bank Syariah? Penelitian ini bertujuan untuk mengetahui hubungan antara karakteristik Dewan Pengawas Syariah (DPS) dan Good Corporate Governance (GCG) terhadap kinerja Bank Syariah (BS) di Indonesia. Data dikumpulkan dari 14 BS yang terdaftar di OJK selama periode 2013-2019. Berdasarkan hasil regresi berganda secara empiris menunjukkan bahwa DPS yang memiliki jabatan akademik sebagai profesor menunjukkan hubungan positif yang signifikan dengan kinerja BS. Sedangkan DPS dengan pendidikan doktor tidak memiliki hubungan positif dengan kinerja BS. Walaupun tidak berkorelasi positif, pendidikan doktor tetap diperlukan tetapi dengan latar belakang pendidikan hukum atau syariah, ekonomi termasuk keuangan atau akuntansi, dan muamalah. Karena latar belakang pendidikan tersebut terbukti memiliki hubungan positif yang signifikan dengan kinerja BS. Sedangkan DPS yang hanya berlatar belakang keuangan atau akuntansi tidak menunjukkan hubungan positif dengan kinerja BS. Selain itu, GCG menunjukkan hubungan positif yang sangat signifikan dengan kinerja BS. Hal ini menunjukkan bahwa tata kelola yang efektif dan efisien oleh Dewan Direksi, Dewan Komisaris, dan DPS melalui penerapan prinsip-prinsip GCG dan syariah yang lebih baik akan meningkatkan kinerja BS.